Spices and Seasoning Mixes in European Union—Innovations and Ensuring Safety - Maria Śmiechowska; Joanna Newerli-Guz; Magdalena Skotnicka (Foods, 2021)
Spices are an important group of food products of great importance in nutrition and food technology. They are mainly used to shape the sensory properties of food in gastronomy, in home cooking, and in industry. Ensuring quality and safety is one of the basic tasks of spice producers. The aim of this review is to present the threats to the consumer related to the presence of spices and seasoning mixes in the diet. Therefore, special attention was paid to such risks as excess sodium chloride (and sodium) in spice mixtures, the use of additives influencing the sensory experience, and irregularities in the labeling of spices and seasoning mixes for the presence of additives and allergens. The threats regarding microbiological safety and the presence of heavy metals, pesticides, plant protection products, as well as synthetic fertilizers and undeclared additives are also presented and the issue of adulteration and lack of authenticity of spices and spice mixtures is discussed. Using data from IJHARS planned inspections and notifications registered in the EU Rapid Alert System for Food and Feed (RASFF) for 2015–2019, as well as the results of own research, an analysis of the risks caused by herbs and spices was carried out. Strategic activities of companies producing spices focus, among others, on improving production and expanding the commercial offer with new, attractive products. The article reviews product and process innovations in spice mixes and the methods of ensuring safety in this group of food products.